A Comparative Study of Safavid Fabric Designs with Miniatures in School of Second Tabriz (With a focus on the Works of Sultan Mohammad, Mir-Musavvir and Mir-Sayyid Ali) - Hoseini, Seyed Reza; Sepasi, Zohreh (Journal of History Culture and Art Research, 2018)
Iranians experienced a golden age of textile art-industry during the Safavid period. In terms of beauty, design, colour and configuration, textiles of this period are influenced by the style of the painters who had a realistic tendency and paid attention to natural elements to represent thoroughly the external world in small logs. Early in Safavid era, the school of second Tabriz was established to mark a historic turning point in Iran’s painting. What we observe is a good cooperation between painters and weavers in designing fabric motifs that led to producing the most beautiful, irreplaceable and priceless fabrics, brocade, velvet and silk in the world. The purpose of this study is to examine the impact of three painters of Tabriz School (Sultan Mohammad, Mir-Musavvir and Mir Sayyid Ali) on the design of fabrics, and match the images and motifs designed by them. The main research questions are as follows: 1) what relationship exists between the designs of initial Safavid fabrics and Persian painting in second Tabriz School? 2) Were the fabric motifs in early Safavid designed by painters of second Tabriz School? This study examines the impact of Tabriz School painters on two areas of main and background fabric designs, which are divided into two groups of abstract and realistic. The results of matching fabric samples remained from the well-known painters of that era show textile designs by those painters, and it can be stated that artists like Sultan Muhammad, Mir-Musavvir and Mir-Sayyid Ali each followed a particular style in designing fabric motifs in second Tabriz School. This study was based on descriptive - analytical method and data collection was observational through library research.